دور مفتش الشغل في إقرار السلم الاجتماعي: الواقع والآفاق - اكراوي، فاطمة الزهراء (مركز البحث وتطوير الموارد البشرية - رماح, 2022)
مما لا شك فيه أن تباين المصالح المتعارضة بين طرفي علاقة الشغل غالبا ما يؤدي إلى نشوب نزاعات تختلف حدتها ودرجتها باختلاف طبيعتها فردية كانت أو جماعية، ولتفادي تطور هذه النزاعات وما يشوب عنها من مساوئ اجتماعية واقتصادية، حرصت مختلف التشريعات على سن قواعد قانونية كفيلة بتسويتها بشكل سلمي دون الحاجة للجوء إلى القضاء، وذلك من خلال جهاز تفتيش الشغل الذي أصبحت مهمته تتجاوز حد المراقبة لتشمل التدخل لحل نزاعات الشغل وتحقيق السلم الاجتماعي. وعليه فإن هذه المقالة ستنكب حول تسليط الضوء على دور مفتش الشغل في إقرار السلم الاجتماعي، وتوضيح ذلك رهين بتحديد الإطار القانوني للاختصاص التصالحي لمفتش الشغل مع إبراز الآراء المتضاربة حول إسناد هذا الاختصاص لهذا الجهاز، إضافة إلى بيان الأساس القانوني للوظيفة التصالحية على مستوى نزاعات الشغل الفردية والجماعية هذا من جهة، ومن جهة أخرى حاولنا تقييم مدى نجاعة دور مفتش الشغل في إقرار السلم الاجتماعي، دون أن نغفل الإشارة إلى الإكراهات التي تحد من فعالية هذا الدور، لنخلص في الأخير إلى بعض الحلول والاقتراحات لتجاوزها. There is no doubt that the discrepancy between the conflicting interests between the two parties of the employment relationship often lead to the emergence of conflicts which intensity and degree vary according to their individual or collective nature. In order to avoid the development of these conflicts and the social and economic disadvantages associated with them, various legislations were keen to enact legal rules capable of settling them peacefully without the need to resort to justice. This is done through the labor inspectorate whose mission goes beyond monitoring to include intervention to resolve labor disputes and achieve social peace. Therefore, this article focuses on the role of the labor inspector in establishing social peace. To clarify this, the legal framework should be defined by restoring to the competence of the labor inspector and highlighting the conflicting opinions about assigning this competence to this organization. In addition to clarifying the legal basis for the conciliatory function at the level of these individual and collective labor disputes, there should be the assessment of the effectiveness of the role of the labor inspector in establishing social peace. There should also be reference to the constraints that limit the effectiveness of this role. The conclusion will be about some solutions and suggestions to overcome these constraints.
Keywords: السلم الاجتماعي -- نزاعات الشغل -- مفتشو الشغل -- القانون المعربي